Prevalence of Listeria monocytogenes infection in women with spontaneous abortion, normal delivery, fertile and infertile - Amjad Ahmadi; Rashid Ramazanzadeh; Safoura Derakhshan; Mazaher Khodabandehloo; Fariba Farhadifar; Daem Roshani; Atefeh Mousavi; Manouchehr Ahmadi Hedayati; Mohammad Taheri (BMC Pregnancy and Childbirth, 2022)
Abstract Background Listeria monocytogenes with a vast range of natural reservoirs is more known for being a food-borne pathogen. Human infections have shown an impact on pregnancy outcomes, so, this study surveyed the frequency of L. monocytogenes infection involving different groups of women. Methods This study enrolled a total sample consisting of 109 women with spontaneous abortion, 109 women with normal delivery, 100 fertile women, and 99 infertile women aged 19–40 years and willing to participate in the study. The research tool in this study was a questionnaire and Polymerase chain reaction (PCR) test. Results According to the results, the frequency of L. monocytogenes infection was 4/109 (3.66%) observed among women with spontaneous abortion, 2/109 (1.83%) among women with normal delivery, 3/100 (3%) among fertile women, and 0/99 (0%) among infertile women. Conclusion There was no significant relationship between Listeria monocytogenes infection and pregnancy outcomes of spontaneous abortion and infertility.